ANTARA HUTAN, INVESTASI, DAN KEMISKINAN: DINAMIKA EMISI KARBON DI INDONESIA - Sari, Cut Putri Mellita; Trisniarti, Noviami; Nailufar, Fanny (Jurnal Ekonomi Pertanian Unimal, 2024)
The study assessed the impact of the proportion of forests, Inland Capital Growth (INC), and the number of poor people on carbon emissions in Indonesia. As a country with extensive tropical forests, Indonesia faces the challenge ofining forest sustainability amid the pressure of economic development. Industrial and infrastructure investments often lead to deforestation, increasing carbon emissions, while poor communities that rely on forests carry out environmentally damaging practices. This research filled the gaps in previous studies by exploring how variations in forest proportions, the impact of GDP in various sectors, and the relationship of poverty with land use affect carbon emissions. The study also examines the interactions between the three variables. The results are expected to provide a comprehensive insight into Indonesia's policy strategy for reducing carbon emissions. The double linear regression analysis method tests the influence between these variables. Data obtained from Indonesian Statistics for the period 2000-2022. The analysis results show that the proportion of forests has a negative and significant influence on carbon emissions, which means that increasing forest size can effectively reduce carbon emissions. Moreover, the PMDN has also been found to have a negative, significant impact on carbon emissions, suggesting that domestic investment plays a role in reducing emissions. On the contrary, the number of poor populations has no significant influence on carbon emissions. These findings indicate that policies to increase the proportion of forests and boost the MDGs can be effective strategies to reduce carbon emissions while reducing the number of poor populations does not directly affect carbon emissions.